Citra Politik Gemoy Capres Prabowo Subianto Menjelang Pilpres 2024 - Sumsari, Dewi; Izomiddin, I; Darmawan, Erik (Jurnal Studi Ilmu Politik, 2024)
This Research on Presidential Candidate Prabowo Subianto's gemoy political image ahead of the 2024 presidential election was motivated by the phenomenon of Prabowo's joget gemoy and the massive amount of gemoy comments on every post related to Prabowo on social media, especially TikTok. Therefore, this research aims to find out how the gemoy image of Presidential Candidate Prabowo Subianto emerged and its use in campaign activities. Researchers will dissect the problem using the political image theory proposed by Dan Nimmo. The data in this research is in the form of photos and videos as well as comments from netizens on social media and online news portals. Data was collected using data collection techniques from new media via the internet (Analyzing Virtual Data) by Winfriend Marotzki, Jens Holze and Dan Schnettler applying downloading and taking screenshots. Then it is analyzed using analytical techniques by means of data reduction, data presentation and drawing conclusions by Miles and Hubberman. The results show that the gemoy image comes from the byname from netizens which was then strengthened by Prabowo using the political imaging strategy proposed by Nimmo theory, that is Pure publicity, Free-ride publicity, Tie-in publicity, and Paid publicity. Furthermore, the gemoy image continues to be used in the campaign attributes of Prabowo and the Advanced Indonesia Coalition legislative candidates.